PENINGKATAN PEMAHAMAN MASYARAKAT KELURAHAN SEMARAPURA TENGAH TENTANG TINDAK PIDANA KDRT DAN PERLINDUNGAN ANAK - Yustiawan, D.G.P.; Utami, P.D.Y.; Mayasari, I.D.A.D.; Utari, A.A.S. (Buletin Udayana Mengabdi; Vol 23 No 1 (2024): Buletin Udayana Mengabdi, 2023)
The problem of domestic violence has recently been felt to be increasing, but only a few cases can be disclosed in the public sphere, according to victims of domestic violence, disclosing or reporting acts of domestic violence is tantamount to opening disgrace in domestic relations, because problems in the household are considered taboo and disgraceful. when disclosed to the public. This understanding is what we want to change, that every deviation in domestic violence is something that must receive legal protection. Protection of women in domestic violence as written in Law no. 23 of 2004, it is explained that any action against a woman that results in misery of parents or women, sexual, psychological, and/or neglect of the household is related to activities to carry out coercion or deprivation in household divisions. Apart from domestic violence, the other side of this socialization is regarding child protection, which is regulated in Law no. 35 of 2014 concerning child protection. Where so that people's understanding of the importance of child protection can be applied in social and household life. Keywords: Legal protection, Domestic Violence, Child Protection.